2014
DOI: 10.1186/1748-717x-9-74
|View full text |Cite
|
Sign up to set email alerts
|

Pre-radiotherapy FDG PET predicts radiation pneumonitis in lung cancer

Abstract: BackgroundA retrospective analysis is performed to determine if pre-treatment [18 F]-2-fluoro-2-deoxyglucose positron emission tomography/computed tomography (FDG PET/CT) image derived parameters can predict radiation pneumonitis (RP) clinical symptoms in lung cancer patients.Methods and MaterialsWe retrospectively studied 100 non-small cell lung cancer (NSCLC) patients who underwent FDG PET/CT imaging before initiation of radiotherapy (RT). Pneumonitis symptoms were evaluated using the Common Terminology Crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 57 publications
1
40
2
Order By: Relevance
“…The 95th percentile of the FDG uptake in the lungs remained significant in multivariable logistic regression (p = 0.016; odds ratio [OR] = 4.3). Castillo R et al performed similar work and confirmed that FDG uptake in pre-RT PET predict RILT [92], another potential tool to guide PRT.…”
Section: Image Biomarkersmentioning
confidence: 53%
See 1 more Smart Citation
“…The 95th percentile of the FDG uptake in the lungs remained significant in multivariable logistic regression (p = 0.016; odds ratio [OR] = 4.3). Castillo R et al performed similar work and confirmed that FDG uptake in pre-RT PET predict RILT [92], another potential tool to guide PRT.…”
Section: Image Biomarkersmentioning
confidence: 53%
“…In NSCLC, SUV measures of FDG uptake on the PET image before RT may also be used as a biomarker to predict radiation induced lung toxicity [91,92]. The hypothesis is that pretreatment inflammation in the lung makes pulmonary tissue more susceptible to radiation damage.…”
Section: Image Biomarkersmentioning
confidence: 99%
“…In addition, a review noted that SPECT imaging may be more efficient than planar imaging in estimating overall pulmonary function [20]. According to a retrospective analysis, upper lung lobes have a higher metabolic radiation response compared with lower lobes when taking into account PET results [18]. This study also suggested 5 Gy radiation as a limiting dose -that is, below this level there may not be enough injury to allow observation.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have shown that 18 F-FDG PET additionally predicts which patients will have a tendency for radiation pneumonitis before RT [18]. We already know that 18 F-FDG PET imaging shows early changes related to radiation injury: it is not recommended that 18 F-FDG PET imaging be performed early after RT in routine practice. The rationale for this time delay between imaging and therapy is that considerably increased activity, as a consequence of RT, may obscure other pathologies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation